2019
DOI: 10.26505/djm.16024460122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Invasive and Non-Invasive Methods for the Diagnosis of H. pylori in Dyspepsia Patients

Abstract: Background: H. pylori has been established as the major causative agent of chronic gastritis, and represents the main etiological cause of other gastroduodenal diseases such as peptic ulceration, gastric lymphoma, and gastric cancer. Therefore, screening and treatment of the bacterium is an important strategy for preventing gastric cancer. Objective: To compare some invasive classical histological tests to non-invasive serological antibody and stool antigen tests for the diagnosis of H. pylori infections. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…Giemsa stain is a simple, rapid and inexpensive stain that has good sensitivity, specificity and consistency in the detection of H. pylori infection ( 13 , 27 , 33 , 34 ). Therefore, it is routinely used in some institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giemsa stain is a simple, rapid and inexpensive stain that has good sensitivity, specificity and consistency in the detection of H. pylori infection ( 13 , 27 , 33 , 34 ). Therefore, it is routinely used in some institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is routinely used in some institutions. According to many scientific papers, Giemsa stain is superior to H&E in the detection of H. pylori ( 13 , 27 , 30 , 33 , 34 ). Based on our findings, the sensitivity of Giemsa stain in the detection of H. pylori is 93.33% while its specificity is 100%, which makes it better than H&E and PAS-AB stains.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 Clinically, a variety of various invasive techniques (requiring endoscopy and biopsy which include, culture, histological examination, and rapid urease test, CLO (Campylobacter like organism) test, smear examination, and molecular studies) or noninvasive techniques (including serology, respiratory urea breath test, or the detection of fecal antigen) are often performed to detect H. pylori infection. [9][10][11] The sensitivity of any of those techniques in detecting H. pylori relays on how the density of the bacterial cells within the specimens taken by biopsy (recent use of disease-related medications, specifically antibiotics and protonpump inhibitors (PPI) can reduce the density of the cells), pathologist expertise, also the type and quality of the stain used for detection purposes. 10 Many studies reported that the gold standard method for the diagnosis is the detection of H. pylori in biopsy material.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The sensitivity of any of those techniques in detecting H. pylori relays on how the density of the bacterial cells within the specimens taken by biopsy (recent use of disease-related medications, specifically antibiotics and protonpump inhibitors (PPI) can reduce the density of the cells), pathologist expertise, also the type and quality of the stain used for detection purposes. 10 Many studies reported that the gold standard method for the diagnosis is the detection of H. pylori in biopsy material. 12,13 Currently, many clinical laboratories use urease tests and histological analysis as a gold standard approach.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, H. pylori may be implicated in several extra-gastric diseases such as iron de ciency anemia, idiopathic thrombocytopenic purpura, and several dermatological disorders (Chmiela et al, 2017, Kodaman et al, 2014, Testerman and Morris, 2014. Its distribution is worldwide and affects more than 90% of the world population, but it is more common in developing countries with the highest prevalence found in Africa (Idris et al, 2021, Zamani et al, 2018, probably due to the possible transmission through fecal-oral route and the unsafe sanitation conditions in these countries (Eldeen et al, 2019, Nevoa et al, 2017.Clinically, a variety of various invasive techniques (requiring endoscopy and biopsy which include, culture, histological examination, and rapid urease test, CLO (Campylobacter like organism) test, smear examination, and molecular studies) or noninvasive techniques (including serology, respiratory urea breath test, or the detection of fecal antigen) are often performed to detect H. pylori infection (Akanda and Rahman, 2011, Mawlood et al, 2019, Wang et al, 2015. The sensitivity of any of those techniques in detecting H. pylori relays on how the density of the bacterial cells within the specimens taken by biopsy (recent use of disease related medications speci cally antibiotics and proton-pump inhibitors can reduce the density of the cells), pathologist expertise, also the type and quality of the stain used for detection purposes (Mawlood et al, 2019).…”
Section: Introductionmentioning
confidence: 99%